Analysis of Pilot-ATC Communication Factors in Aircraft Accidents and Incidents: A Literature Review from The Perspective of ATS Safety Investigations - Rizka Aprilia Ardani; Elfi Amir; Rani Adiliawijaya Putriekapuja (Green Publisher Indonesia, 2026)
Flight safety is greatly influenced by the effectiveness of communication between pilots and Air Traffic Controllers (ATC). In many aircraft accidents and incidents, communication failures, readback/hearback errors, the use of non-standard phraseology, and limited situational awareness are significant contributing factors. This research aims to analyze the literature related to the relationship between pilot-ATC communication and aircraft accident and incident incidents, especially in the context of Air Traffic Services Safety Investigation. The method used was literature review with stages of identification, selection, analysis, and synthesis of literature from investigation reports, scientific articles, and international aviation safety documents. The results of the study show that unclear communication can trigger runway incursion, loss of separation, clearance errors, and delayed decision-making. Case studies such as the Tenerife Airport Disaster show that a combination of miscommunication, operational pressures, weather, and technological limitations can develop into fatal accidents. The conclusion of this study emphasizes the importance of standardization of phraseology, improving human factors training, implementing readback/hearback discipline, and strengthening safety support systems in ATS operations.